2022
DOI: 10.21203/rs.3.rs-1466387/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors of nosocomial Covid-19 in a French university hospital: a case- control study

Abstract: Background: During the Covid-19 pandemic, prevention strategies implemented by hospitals to reduce nosocomial transmission sometimes failed and determining transmission risk factors remains crucial. Our objective was to determine the risk factors of nosocomial Covid-19.Methods: A case-control study was conducted in a French hospital between 09/01/2020 and 01/31/2021. Adult patients hospitalized in medical or surgical units were included. Infants or patients hospitalized in ICU were excluded. Cases were patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The retrospective nature of our case-control study precludes conclusions There have been many reports on hospital-based outbreaks of COVID-19 [4, 25, 27-29, 31, 39, 52-56], however a strength of our report is that it incorporated a case-control study to explore contributing ward and patient-related factors to the acquisition of COVID-19, occurring in a setting without vaccination for any HCWs or patients. Our outbreak has similarities with other COVID-19 nosocomial outbreaks including unidentified cases on a ward [39,56], positive HCWs who may have sub-optimal adherence to IPC measures [52,54], and the role of multi-bedded rooms in SARS-CoV-2 transmission [27,29,31,34,35] Further, our report included patient symptoms, environmental sampling, whole genome sequencing, viral culture and has identified the novel finding of fluid and electrolyte disorders increasing the likelihood of COVID-19 acquisition.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The retrospective nature of our case-control study precludes conclusions There have been many reports on hospital-based outbreaks of COVID-19 [4, 25, 27-29, 31, 39, 52-56], however a strength of our report is that it incorporated a case-control study to explore contributing ward and patient-related factors to the acquisition of COVID-19, occurring in a setting without vaccination for any HCWs or patients. Our outbreak has similarities with other COVID-19 nosocomial outbreaks including unidentified cases on a ward [39,56], positive HCWs who may have sub-optimal adherence to IPC measures [52,54], and the role of multi-bedded rooms in SARS-CoV-2 transmission [27,29,31,34,35] Further, our report included patient symptoms, environmental sampling, whole genome sequencing, viral culture and has identified the novel finding of fluid and electrolyte disorders increasing the likelihood of COVID-19 acquisition.…”
Section: Discussionmentioning
confidence: 58%
“…Based on our findings, patients who spent > 50% of their admission in a multi-bedded room had 3.2 times the rate of acquiring COVID-19. Other observational studies have demonstrated that multi-bedded rooms versus one-to-two bedded rooms and the use of shared toilets were more common among nosocomial COVID-19 cases compared to controls [29,31,34,35]. The duration of time in a multi-bedded room was a major risk factor and the finding of a dose-response relationship adds epidemiologic strength of association to this finding.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation